Effects of re-curing on residual mechanical properties of concrete after high temperature exposure - Akca, Abdullah Huzeyfe; Ozyurt, Nilufer (ELSEVIER SCI LTD, 2018)
Physical and mechanical changes in concrete continue in subsequent days of heating since some chemically active products in concrete give reactions with water and carbon dioxide in air and new formations determine the fate of concrete. Therefore, this study was conducted to understand the effects of mineral admixtures, fiber reinforcement, air entrainment and different re-curing regimes (after heating) on residual properties of concrete. Concrete specimens were heated to 1000 C then water and air re-curing processes were applied on heated specimens and further deterioration and recovery of concrete were evaluated. New cracks occurred on the heated surfaces during air re-curing period and reduction in mechanical properties was observed while water re-cured specimens kept their stabilities and regain in their mechanical properties was obtained. Moreover, micro level investigations were conducted on heated surfaces of air re-cured and water re-cured concrete specimens for understanding the reasons of changes observed in mechanical properties. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: High temperature; Fiber reinforced concrete; Recovery; Deterioration; Air entrainment; HIGH-STRENGTH CONCRETE; HIGH-PERFORMANCE CONCRETE; FIRE-DAMAGED CONCRETE; CEMENT PASTE; COMPRESSIVE STRENGTH; THERMAL-CONDUCTIVITY; ELEVATED-TEMPERATURE; BEHAVIOR; MICROSTRUCTURE; CARBONATION; Construction & Building Technology; Engineering; Materials Science